Coexistence of Aplasia Cutis and Nevus Psiloliparus-Report of a Novel Case - YÜCELTEN, AYŞE DENİZ; EKİNCİ, GAZANFER (WILEY-BLACKWELL, 2014)
Nevus psiloliparus is a type of mesodermal nevus of the scalp classically seen with encephalocraniocutaneous lipomatosis. The close association between nevus psiloliparus and aplasia cutis congenita is called didymosis aplasticopsilolipara. Although typically associated with neurologic, ocular, and skeletal findings, didymosis aplasticopsilolipara can be seen without the context of encephalocraniocutaneous lipomatosis.
Keywords: DIDYMOSIS